Intracellular Staphylococcus aureus: the Trojan horse of recalcitrant chronic rhinosinusitis?. Issue 4 (19th February 2013) - Tan, Neil C.‐W.; Foreman, Andrew; Jardeleza, Camille; Douglas, Richard; Vreugde, Sarah; Wormald, Peter‐John
<x xml:space="preserve">Abstract</x> Background Despite recent evidence suggesting that Staphylococcus aureus exists within the sinonasal epithelium of chronic rhinosinusitis (CRS) patients, certain questions remain. The intracellular environment may provide a protective niche for pathogenic bacteria to evade host immunity and yet provide a reservoir for reinfection. To date, no studies have examined the impact of this bacterial phenotype; therefore, this study was designed to evaluate the role of intracellular S. aureus on postsurgical outcomes. Methods This study included 51 patients undergoing endoscopic sinus surgery (ESS) for medically‐recalcitrant CRS. Sinonasal mucosa harvested at the time of surgery was dually stained with fluorescent molecular probes and imaged using confocal scanning laser microscopy for biofilm and intracellular status. Patients were followed in their early and late postoperative course for evidence of ongoing disease and signs of clinical relapse. Results Intracellular S. aureus was identified in 20 of 51 (39%) patients, and all were associated with surface biofilm. Biofilm alone was found in 16 of 51 (31%) patients and 15 of 51 (29%) patients had no evidence of S. aureus. Intracellular positive patients had a significantly higher risk of late clinical and microbiological relapse (p = 0.014). In this study, biofilm status without coexisting intracellular bacteria did not appear to impact on outcomes. Conclusion Clinical and microbiological relapse of disease following ESS is significantly associated with intracellular S. aureus. Evidence suggests that this disease association is independent to surface biofilm status. Intracellular bacteria should be taken into consideration when designing novel treatment strategies to lessen the chance of reinfection.